ANALYSIS OF PESANTREN HEALTH POST MANAGEMENT (POSKESTREN) AT DARUSSALAM ISLAMIC BOARDING SCHOOL PURWOKERTO - Sugeng Riyadi; Abdul Basit (Nindikayla Institute, 2023)
Background: One form of empowerment in Islamic boarding schools is by developing Pesantren Health Posts (Poskestren). However, it is still rare for Islamic boarding schools to have Poskestren. In Banyumas Regency, there are only 27.5% of Islamic boarding schools that have Poskestren. Poskestren Darussalam is a Poskestren that grows and develops in order to improve the quality and health of students. This study aims to analyze the success of the implementation of the Darussalam Poskestren Program in the hope that it will be a lesson for other Poskestren. Method: Data collection in this qualitative descriptive research was conducted by in-depth interviews and field observations. The research subjects consisted of 8 Poskestren cadres with purposive sampling method. The validity of the data was done by interviews with nine triangulation subjects. Data reliability is carried out by data auditing and data analysis using content analysis methods. Results: In the input aspect, the number of cadres is sufficient, medical equipment is complete but for the special room Poskestren is still under construction. The availability of funds is sufficient and most of them come from outside parties. There are basic personal hygiene data and health information media. In addition, there is kiai support in implementing policies that support Poskestren activities. In the process aspect, the Self-Awareness Survey (SMD) and Islamic Boarding School Community Deliberation (MMPD) activities have been carried out. Poskestren activities consist of promotive, preventive, curative and rehabilitative efforts. Then there is synergy with Puskesmas Kembar I which is actively building Poskestren. Conclusion: Based on the success indicators of Poskestren, it shows that from the aspect of input and overall process has been fulfilled so that Poskestren Darussalam is included in the good category, but needs improvement in terms of the formation of special divisions of Poskestren and the provision of special rooms for Poskestren. So it is hoped that Poskestren Darussalam will be even better.